PROSES DIPLOMASI MUSIK INDONESIA TERHADAP JEPANG MELALUI ENOSHIMA BALI SUNSET FESTIVAL PADA TAHUN 2010 - Talava, I Made Arthya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
This research aims to describe the role of cultural diplomacy through the medium of music, in the event of Enoshima Bali Sunset Festival 2010. Enoshima Bali Sunset Festival 2010 is an annual project that was organized by Sanggar Basundhari to introduce Balinese arts and culture in Japan. On 2010, Arti Foundation invited to be one of the performers in this event. Arti Foundation accepted this invitation with support by the Government of the City of Denpasar, with hope that the performance could introduce the values of Balinese arts and cultures in Japan and also promote Denpasar City as “Kota Kreatif Berbasis Budaya Unggulan”. Cosmopolitan Constructivism, Intercultural Understanding, and Musical Diplomacy are the concept tha the writer use in this research. Keywords: Cultural Diplomacy, Musical Diplomacy, Enoshima Bali Sunset Festival